Legally straight : sexuality, childhood, and the cultural value of marriage - Rollins, Joe, 1961- (New York : New York University Press, 2018)
'Legally Straight' offers a critical reading of the legal debates over lesbian and gay marriage in the United States. The book draws on key judicial opinions to trace how our understanding of heterosexuality and marriage has changed.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 27, 2018).
Keywords: Same-sex marriage -- Law and legislation -- United States -- History; Sex and law -- United States -- History; Sociological jurisprudence -- United States -- History; Marriage -- Social aspects -- United States -- History; Same-sex marriage -- Social aspects -- United States -- History; Sex -- Social aspects -- United States -- History; Children and sex -- United States -- History; Law; Laws of specific jurisdictions & specific areas of law; Family law: marriage, separation & divorce; Family law: children